Korelasi antara Kemampuan Membaca Kitab Kuning dengan Kepribadian Siswa SMA An-Nur Bululawang Malang - Saiul Ana (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
The research objective of the Correlation Between the Ability to Read the Yellow Book and the Personality of An-Nur High School Students in Bululawang Malang: 1). Knowing the yellow book learning at SMA An-Nur Bululawang Malang. 2). Knowing the ability to read the yellow book of An-Nur Bululawang Malang high school students. 3). Test the correlation between the ability to read the yellow book with the student's personality. This study uses a quantitative approach and the research design is a survey model in which the type of research is correlation research. Correlational research aims to detect the extent to which variations in one factor are related to variations in other factors based on their correlation coefficient. data collection methods used are documentation and questionnaires. The substantive findings of this research are: 1). Yellow book learning at SMA An-Nur Bululawang Malang using the Sorogan, Bandongan, Wetonan, and Muzakaroh methods. 2). The better the ability to read the yellow book, the better the personality of the students at SMA An-Nur Bululawang Malang. 3). Meanwhile, to test the correlation between the ability to read the yellow book, the better the personality of the students at SMA An-Nur Bululawang Malang. The formal findings of this researcher are: In general, the effect of the better the ability to read the yellow book, the better the personality of the students at SMA An-Nur Bululawang Malang at a good level, the level of the ability to read the yellow book, the better the personality of the student. in SMA An-Nur Bululawang Malang is in the good category, and the correlation coefficient between the method of division of tasks and student achievement (rXY) is 0.788. This r value is consulted with the product moment table r value with N = 158 and a significance level of 5%, namely 0.676, it is proven that r count is greater than r table so that the proposed hypothesis must be accepted.